1998
DOI: 10.1007/s003359900890
|View full text |Cite
|
Sign up to set email alerts
|

Homology between human Chromosome 2p13.3 and the wobbler critical region on mouse Chromosome 11: comparative high-resolution mapping of STS and EST loci on YAC/BAC contigs

Abstract: Human Chr 2p13-14 and homologous regions on mouse Chrs 6 and 11 have been subjects of previous studies because they comprise the loci for several neuromuscular diseases. Here we report on high-resolution mapping of 55 STS and EST loci on human Chr 2p13.3 and of 47 markers on the corresponding region on proximal mouse Chr. 11. The maps comprise several known genes, MEIS1/Meis1, RAB1a/Rab1a, MDH1/Mor2, OTX1/Otx1, and REL on human 2p13.3 and mouse Chr 11, respectively, as well as the wobbler (wr) critical region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…A literature survey shows that mutations of the proximal regions of chromosomes 2 and 11 are associated with cerebellar ataxias. The critical regions for the Stumbler and Wobbler ataxia models map to the proximal regions of chromosomes 2 and 11, respectively (Frankel et al 1994;Resch et al 1998).…”
Section: Spatial Distribution Of Neuronal Centromeresmentioning
confidence: 99%
“…A literature survey shows that mutations of the proximal regions of chromosomes 2 and 11 are associated with cerebellar ataxias. The critical regions for the Stumbler and Wobbler ataxia models map to the proximal regions of chromosomes 2 and 11, respectively (Frankel et al 1994;Resch et al 1998).…”
Section: Spatial Distribution Of Neuronal Centromeresmentioning
confidence: 99%
“…So far Pellino homologues have been identified in Caenorhabditis elegans (Rich et al, 2000) and the urochordate Ciona intestinalis, in which expression was found in the notochord (Hotta et al, 2000). In the course of the positional cloning of the neurological mutation wobbler of the mouse (Resch et al, 1998) we found an EST homologous to the Drosophila gene coding for Pellino. We therefore isolated cDNAs and characterized the genes of Pellino homologues in man and mouse.…”
Section: Rationale and Significancementioning
confidence: 98%
“…Mapping of Pellino 1 was performed physically on well-established YAC contigs of mouse and man (Resch et al, 1998). Pellino 2 was mapped by radiation hybrids using GeneBridge4 RH Panel for man and T31 mouse/ hamster radiation hybrid panel for mouse, both panels were obtained from Research Genetics (Huntsville).…”
Section: Methodsmentioning
confidence: 99%
“…The wobbler mouse is an animal model of importance since it is considered as a model for sALS, representing approximately 90% of all ALS cases [7][8][9], although the wobbler mutation does not seem to be a common reason for ALS [10,11]. Palmisano and co-workers described enlarged vesicles in wobbler mice α-motor neurons (αMN) [12], which indicate an impaired trafficking in wobbler mice, like six out of fourteen human sALS cases.…”
Section: Immunofluorescence Staining Of Nfh/pnfhmentioning
confidence: 99%